Examining a Canadian Jazz Icon: Pitch-Class Hierarchy in Some Representative Examples of Kenny Wheeler - Cook, Scott (Intersections, 2012)
The article examines some representative tunes by the notable Canadian jazz trumpeter and composer Kenny Wheeler. Though rooted in traditional jazz practices, Wheeler’s own compositions often deviate from tradition. For instance, his chord successions are sometimes highly chromatic and often non-diatonic. Further, he often excludes Mm7 chords, which diminishes the sense of traditional functionality. Yet his melodies tend to promote longer-reaching relationships that prioritize certain pitch-class collections over others. In contrast to the more traditional chord-scale approach commonly used to analyze jazz tunes, the prime goal of the article will be to show how continuity across less-conventional chord successions is conceivable when taking a top-down analytical approach—that is, when prioritizing the melody.